Pasteurella multocida bacteremia in a patient with septic arthritis - Shikha Malhotra; Tung Phan (Infectious Medicine, 2022)
Pasteurella multocida is a common commensal microorganism found in the nasopharynx of domestic and wild animals. Humans acquire P multocida infection primarily through contact with animals or their mucous secretions. P multocida is infrequently encountered in clinical settings, and it is considered as a zoonotic pathogen. In this study, we present an interesting case of septic arthritis and bacteremia caused by P multocida in a 62-year-old patient. The patient was treated with surgical procedures and antibiotic therapy, which made significant improvement. This case study highlights the importance of P multocida in causing zoonotic infection in humans.